2021
DOI: 10.31234/osf.io/uamwg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visible Garden Biodiversity Leads to an Increase in Noticing Nature, Which in Turn Leads to an Increase in Nature Connectedness

Abstract: A strong connection to nature promotes behaviours that help conserve the natural world. However, it is likely that this relationship is reciprocal, with the pathways to nature connectedness including care for nature through pro-nature conservation behaviours and sensory contact with nature. Pro-conservation behaviours vary in terms of how much visible biodiversity, and therefore contact with nature, they produce. It is likely that conservation behaviours that support higher visible biodiversity will result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…In contrast to environmental volunteering, citizen science, or community gardening, picking up litter is a relatively quick and simple behavior that provides immediate feedback and has been associated with personal and social norms (The Behavioural Insights Team 2014, Gould et al 2016) -it may therefore be a behavior that is generally more likely to occur. Further, while previous research has demonstrated associations between CN and environmental volunteering (Guiney and Oberhauser 2010), citizen science (Chase and Levine 2017), and gardening practices (Hamlin and Richardson 2021), the current findings suggest that the pathways linking these constructs are likely more intricate than a simple moderation via concepts of nature. Exploring other potential moderators and/or mediators of the CN-PBB relationship(s) could be a useful avenue for future research.…”
Section: Concepts Of Nature As Moderator Between Cn and Pbbcontrasting
confidence: 64%
See 1 more Smart Citation
“…In contrast to environmental volunteering, citizen science, or community gardening, picking up litter is a relatively quick and simple behavior that provides immediate feedback and has been associated with personal and social norms (The Behavioural Insights Team 2014, Gould et al 2016) -it may therefore be a behavior that is generally more likely to occur. Further, while previous research has demonstrated associations between CN and environmental volunteering (Guiney and Oberhauser 2010), citizen science (Chase and Levine 2017), and gardening practices (Hamlin and Richardson 2021), the current findings suggest that the pathways linking these constructs are likely more intricate than a simple moderation via concepts of nature. Exploring other potential moderators and/or mediators of the CN-PBB relationship(s) could be a useful avenue for future research.…”
Section: Concepts Of Nature As Moderator Between Cn and Pbbcontrasting
confidence: 64%
“…Evidence suggests that different CN dimensions may have different relationships with some PBB (Hatty et al 2020), indicating that further exploration of CN dimensions as antecedent PBBs is warranted. Further, the relationship between CN and PBB is likely reciprocal (Richardson and Hamlin 2021), thus future research should investigate CN and PBB as both antecedent (X) and consequent (Y) in moderation/mediation analyses.…”
Section: Limitations and Future Researchmentioning
confidence: 99%